Heating Greenhouses - Jonathan A. Watson; Celina Gómez; D. E. Buffington; Ray A. Bucklin; Richard W. Henley; Dennis B. McConnell (EDIS)
A greenhouse has one purpose: to provide and maintain the environment that will result in optimum crop production for maximum profit. This includes an environment for work efficiency as well as for crop growth. This publication is limited to describing equipment and methods used to control or maintain desirable temperature in a greenhouse during those periods when supplemental heat is required. There are many ways this can be accomplished from the standpoint of equipment used, type of fuel and construction used, and management practices followed. Because each operation usually has some unique characteristics, such as types of plants produced, level of desired production quality, type(s) of greenhouse(s) used, and management procedures followed, it is important that all of these factors be considered when selecting and installing a heating system. This 5-page fact sheet is a minor revision written by J. A. Watson, C. Gómez, D. E. Buffington, R. A. Bucklin, R. W. Henley, and D. B. McConnell, and published by the Department of Agricultural and Biological Engineering, November 2019.